2014
DOI: 10.1016/j.appet.2014.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with choice of a low-fat or low-carbohydrate diet during a behavioral weight loss intervention

Abstract: Individuals undertaking a weight loss effort have a choice among proven dietary approaches. Factors contributing to choice of either a low-fat/low-calorie diet or a low-carbohydrate diet, two of the most studied and popular dietary approaches, are unknown. The current study used data from participants randomized to the 'choice' arm of a trial examining whether being able to choose a diet regimen yields higher weight loss than being randomly assigned to a diet. At study entry, participants attended a group sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
(31 reference statements)
0
20
0
Order By: Relevance
“…Then, participants were scheduled in their first group weight loss session for the following week, either for the low-fat diet or low-carbohydrate diet. Factors associated with diet selection have been reported, which included food preferences as well as other factors (e.g., expected health benefits; McVay et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, participants were scheduled in their first group weight loss session for the following week, either for the low-fat diet or low-carbohydrate diet. Factors associated with diet selection have been reported, which included food preferences as well as other factors (e.g., expected health benefits; McVay et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…We conducted Aim 1 analyses exclusively in the ‘no choice’ condition in order to take advantage of randomization, which ensures that there is not confounding due to self-selection of diet that had occurred in the diet choice condition. This is particularly important in this study given that diet selection in the diet choice condition was associated with dietary preferences (McVay et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…23 (12) 13 (7) 21 (10) 15 (8) 36 weeks 24 (13) 12 (4) 22 (10) 15 (9) 48 weeks 25 (14) 12 (5) 21 (10) 17 (12) Saturated fat, % daily kcal Baseline 66 (30) 63 (26) 88 (60) 12 weeks 62 (33) 43 (22) 67 (34) 61 (34) 24 weeks 59 (34) 46 (23) 53 (27) 51 (27) 36 weeks 62 (36) 44 (15) 55 (25) 54 (28) 48 weeks 61 (34) 43 (20) 53 (27) 55 (31) Protein, % daily kcal Estimated mean weight trajectories in kg over 48 weeks for the Choice and Comparator arms from linear mixed models. Table 1 Baseline participant characteristics (11) 54 (11) 55 (10) 49 (13) 55 (10) 57 (10) 47 ( 109 (21) 109 (22) 108 (16) 108 (19) 107 (19) 112 (22) Body mass index, kg/m 2 36 (6) 36 (6) 36 (7) 35 (4) 36 (5) 36 (5) 37 ( 46 …”
Section: (67)mentioning
confidence: 99%
“…LCD was originally developed by Bernstein, Atkins and others, 1,2 and now it becomes a universal topic of discussion. [3][4][5][6][7][8] The Japanese Dietetic Association recommended taking 50-60 % carbohydrate, but our group treated DM patients by LCD with 12% carbohydrate since 1999, and experienced a good response and prognosis. [9][10][11][12][13] LCD often accompanied with increase of ketone bodies as a toxic substance, but recent study found the physiological role of beta-hydroxybutyrate, especially in the normal delivery and very low carbohydrate treatment was effective to treat gestational diabetes.…”
Section: Introductionmentioning
confidence: 99%